2016
DOI: 10.1128/aem.01166-16
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy Is Effective in a Mouse Model of Bacterial Equine Keratitis

Abstract: Bacterial keratitis of the horse is mainly caused by staphylococci, streptococci, and pseudomonads. Of these bacteria, Pseudomonas aeruginosa sometimes causes rapid corneal corruption and, in some cases, blindness. Antimicrobial resistance can make treatment very difficult. Therefore, new strategies to control bacterial infection are required. A bacteriophage (phage) is a virus that specifically infects and kills bacteria. Since phage often can lyse antibiotic-resistant bacteria because the killing mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…In a number of liquid infection studies, it has been shown that the initial phage-driven decline of P. aeruginosa was followed by regrowth of bacterial populations, indicative of the evolvement of phage resistance [ 28 , 42 , 43 , 44 , 45 , 47 , 51 , 52 ]. This observation differs from our study, as regrowth after decline of bacteria did not occur within the timeframe of the experiment (except for phage SL1 and strain MDR-PA4, Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of liquid infection studies, it has been shown that the initial phage-driven decline of P. aeruginosa was followed by regrowth of bacterial populations, indicative of the evolvement of phage resistance [ 28 , 42 , 43 , 44 , 45 , 47 , 51 , 52 ]. This observation differs from our study, as regrowth after decline of bacteria did not occur within the timeframe of the experiment (except for phage SL1 and strain MDR-PA4, Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, among others, it is crucial that we begin to develop new treatments to combat bacterial infection. Researchers have already begun investigating potential new antimicrobial strategies (22), such as the use of antimicrobial peptides (23, 24), phage therapy (25, 26), and gene-editing enzymes (27, 28). Here, we report another promising novel approach: the use of predatory bacteria to control Gram-negative human pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was carried out, according to a previously reported method [ 28 , 29 ]. A 5-µL aliquot of phage suspension (10 10 plaque-forming units (PFU)/mL) was dropped onto a double-layer agar plate containing an S. aureus strain.…”
Section: Methodsmentioning
confidence: 99%
“…The pellet was resuspended and diluted in PBS to a density of 2 × 10 6 CFU/mL. Phage was isolated by large-scale culture using soft agar plate, and the phage suspension was purified by density gradient ultracentrifugation using CsCl, according to a previously reported method [ 29 ]. Mice were anesthetized 30 min before infection with a mixture of three types of anesthetic agents: 6 mg/kg midazolam (Dormicum; Astellas, Tokyo, Japan), 0.45 mg/kg medetomidine (Dorbene; Kyoritsu Seiyaku Corp., Tokyo, Japan), and 7.5 mg/kg butorphanol (Vetorpale; Meiji Seika Pharma Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%